HUBUNGAN TINGKAT USIA ANAK DENGAN HARAPAN IBU BEKERJA TERHADAP PELAYANAN TAMAN PENITIPAN ANAK (TPA) - Sulastri " "; Oswati " Hasanah; Rismadefi " Woferst (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2016)
Abstract The increasing of working mothers make parenting time to be reduced. This condition causes the mother's need to find alternative child care. Day care center is alternative option of the parents. Each parent has different expectations for TPA services. The aim of this research was to identify the relationship between child's age level with expectations of mothers to day care center service in Tampan districts Pekanbaru city. The research used correlation descriptive method with cross sectional design. In this research used 78 respondents with cluster sampling. The instrument in this research was a questionnaire that has been tested it’s validity and reliability. The univariate analysis results show the respondent with has infant child and high expectations were 2 respondent (2,6%). The respondent with has toddler child and high expectations were 24 respondent (30,8%) and the respondent has pre school child and high expectations were 10 respondent (12,8%). The Bivariate analysis used Chi square test was obtained p value 0.045> (α = 0.05), it means that there was a relationship between child's age level with expectations of working mothers to day care center service. The results of this research suggest to day care center to give optimum service by providing caregivers which has ability to apply the curriculum of TPA, has educational backgrounds correspond with the terms specified and  has capable of understanding and stimulating growth and development of children according to age level.  Keywords: Child's age level, day care center, expectations